2018
DOI: 10.1007/s13197-018-3401-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of thermo-ultrasound and cinnamon leaf essential oil to inactivate Saccharomyces cerevisiae in culture broth and natural orange juice

Abstract: The survival of Sacharomyces cerevisiae in Trypticase Soy Broth and natural orange juice processed by combined use of thermo-ultrasound and cinnamon leaf essential oil has been evaluated and modelled. Minimal inhibitory concentration of cinnamon leaf essential oil against S. cerevisiae was determined using absorbance measurements based on the microtiter plate assay. The resistance of S. cerevisiae cells to the combined action of thermal treatment with ultrasound was analyzed in Trypticase Soy Broth with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…is widely used as a flavoring agent due to its inhibitory effects against pathogenic bacteria, fungi, viruses, and spoilage organisms. The results showed that the combination of essential oil and US at 50 °C (2.52 log reduction) was effective for orange juice decontamination compared with untreated samples as the control group (1.32 log reduction) [40] . In another study, US with the power of 400 W were used for the process of loquat fruit while immersed in per acetic acid (0.4% w/w) at 20 °C for 6 min.…”
Section: Combined Approaches For Fungal Inactivation and Us In Food And Beveragementioning
confidence: 97%
See 3 more Smart Citations
“…is widely used as a flavoring agent due to its inhibitory effects against pathogenic bacteria, fungi, viruses, and spoilage organisms. The results showed that the combination of essential oil and US at 50 °C (2.52 log reduction) was effective for orange juice decontamination compared with untreated samples as the control group (1.32 log reduction) [40] . In another study, US with the power of 400 W were used for the process of loquat fruit while immersed in per acetic acid (0.4% w/w) at 20 °C for 6 min.…”
Section: Combined Approaches For Fungal Inactivation and Us In Food And Beveragementioning
confidence: 97%
“… 5 min of sonication with 40 W/cm 2 intensity: (Mesophilic aerobic bacteria: 4.3 log10 CFU/g reduction) (Lactic acid bacteria: <1 log10 CFU/g reduction) (Coliform: was detected only on fourth storage day (1.7 log 10 CFU/g) and seventh day (1.8 log 10 CFU/g)) Yeast: <10 CFU/g 10 min of sonication with 40 W/cm 2 intensity: Mesophilic aerobic bacteria: reduced by 2.8–5.4 CFU/g Other microorganisms were reduced to below the limit of quantification [45] Fresh Tumeric Electrolyzed water & ultrasound Electrolyzed water from 5% NaCl US frequency: 43 kHz treatment time: 10 min E.coli , Mesophilic aerobic bacteria, yeast and molds EO 200 mg/L with US at 43 kHz had high value of log reduction on all microorganisms [52] Wheat grain Ultrasound– anolyte medium US frequency: 22–35 kHz US intensity: 0.3 W/cm 2 to 1.5 W/cm 2 Mesophilic aerobic bacteria and fungi Mesophilic aerobic bacteria and Fungi numbers decreased significantly, the use of US with anolyte has shown a synergistic effect. [39] Green asparagus Bath Reactor Ultrasound Frequency: 40 kHz Power: 360 W Treatment time: 10 min stored for 20 days at 4 ˚C Mesophilic aerobic bacteria/ mold and yeast Mesophilic aerobic bacteria, mold and yeast in the 12th and 16th day of storage decreased significantly [48] Chinese cabbage Sweep ultrasound Frequency: 28, 33, 40, and 68 kHz Treatment time: 10 min Mesophilic aerobic bacteria, yeast and molds The significant reduction for mesophilic bacteria was 0.24–1.83 log CFU/g And for yeast and mold was 0.15–2.26 log CFU/g [3] Cucumber Ultrasound Probe Frequency: 20 kHz Treatment time: 5, 10, and 15 min Mesophilic aerobic bacteria and yeast and molds Most significant reduction after 10 min processing [14] Orange Juice Thermo-ultrasound processor with S3 probe Treatment temperature: 50 ˚C Frequency: 24 kHz S. cerevisiae About 1.5 log reduction in S. cerevisiae [40] Lettuce Electric current & Ultrasonic bath Low intensity el...…”
Section: Recent Research Regarding the Application Of Us For Fungal Decontaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, thermosonication can accelerate enzymatic inactivation and sterilization by shortening the treatment time and decreasing the intensity of sterilization and the corresponding negative side effects [ 87 ]. Moreover, the effectiveness of ultrasound can be improved when it is combined with chlorination, extremes of pH, and addition of preservatives [ 88 ].…”
Section: The Use Of Non-thermal Technologies Within the Hurdle Conmentioning
confidence: 99%